Cognitive Validity Of Monologic Presentation As An English Oral Proficiency Assessment Task - Osman, Siti Rafizah Fatimah (2020)
This case study examined the cognitive validity (CV) of monologic presentation (MP), an English oral proficiency assessment task, which is used to assess the oral proficiency of semester 2 diploma students taking EC123 at the institution of higher learning where the researcher is affiliated to. The examination was necessary as no a posteriori validation had been performed to the MP three semesters after its implementation despite the need for validation of assessment instruments/tasks to be done continually and temporally.